SYNERGY BY MOLYBDENUM AND NIOBIUM ON PERFORMANCE OF COLD WORK TOOL STEELS - Aslan Unal (Journal of Sustainable Technologies and Materials, 2025)
For the die industry, where future products have a decisive role in material selection, the subject of steel is an area of interest with high innovation potential. With new production and processing technologies that prioritize knowledge, the quality of materials has improved significantly, and these developments continue. Material selection in die design is a crucial aspect of engineering aimed at developing sustainable and effective solutions to technical challenges. Die manufacturing is open to innovation as the main input is steel. Cold work tool steels (CWTS) are frequently preferred in the die industry. Recently, in addition to traditional CWTS, next-generation CWTS systems have been introduced into use. This article examines the application of one conventional and two next-generation CWTS units as punch tools in sheet metal pressing and thread rolling die for screw manufacturing It has been observed that the new-generation CWTS offers a longer lifespan compared to the traditional one. The microstructures were investigated, and the fine and evenly distributed multiple carbide structures that they can form were evaluated using FactSage® thermodynamic software. The carbides in new-generation CWTS were also rich in molybdenum and niobium. With the use of next-generation materials, modern heat treatments, and advanced coating technologies, it is possible to design specialized products tailored to each specific application. For the innovation approach of modern tool steels in the context of cold-forming dies, traditional and new-generation Cold Work Tool Steels (CWTS) were compared in terms of chemical composition and the use of refractory metals as alloying elements, and their performances were evaluated and interpreted.